2022
DOI: 10.3389/fimmu.2022.1032314
|View full text |Cite
|
Sign up to set email alerts
|

Predictive biomarkers of colon cancer immunotherapy: Present and future

Abstract: Immunotherapy has revolutionized colon cancer treatment. Immune checkpoint inhibitors (ICIs) have shown clinical benefits for colon cancer patients, especially those with high microsatellite instability (MSI-H). In 2020, the US Food and Drug Administration (FDA)-approved ICI pembrolizumab as the first-line treatment for metastatic MSI-H colon cancer patients. Additionally, neoadjuvant immunotherapy has presented efficacy in treating early-stage colon cancer patients. Although MSI has been thought of as an effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 191 publications
0
24
0
Order By: Relevance
“…Future studies will further investigate this topic by evaluating tumor-infiltrating lymphocytes and CXCL14 expression in the tumor microenvironment, especially comparing CDX-2 positive cases with CDX-2 negative cases. It will also be interesting to evaluate PD-L1 expression in CDX2-positive and -negative patients and see if the lack of correlation with response to immunotherapy in mCRC, as described by other works 6,44,46,78 , is confirmed.…”
Section: Discussionmentioning
confidence: 79%
“…Future studies will further investigate this topic by evaluating tumor-infiltrating lymphocytes and CXCL14 expression in the tumor microenvironment, especially comparing CDX-2 positive cases with CDX-2 negative cases. It will also be interesting to evaluate PD-L1 expression in CDX2-positive and -negative patients and see if the lack of correlation with response to immunotherapy in mCRC, as described by other works 6,44,46,78 , is confirmed.…”
Section: Discussionmentioning
confidence: 79%
“…However, ICIs are effective in only a small proportion of patients. Multiple attempts are ongoing to enhance their anti-tumor effects [ 24 , 25 ] or determine their efficacy at an early stage with biomarkers using peripheral blood, tissue samples, and imaging modalities [ 26 , 27 , 28 , 29 , 30 , 31 ]. In 2018, Matson et al reported that the patients’ gut microbiome was associated with their response to ICIs [ 32 ].…”
Section: Immune-related Adverse Events (Iraes)mentioning
confidence: 99%
“…Colorectal cancer (CRC) shows heterogeneous clinical response, and prognostic biomarkers for identifying people at elevated risk of disease recurrence are still underdeveloped [1]. In cases where surgery (and/or neoadjuvant chemoradiation therapy in the rectal cancer setting) may not completely eliminate cancer cells, chemotherapy can be used as adjuvant therapy to reduce the risk of cancer recurrence [2].…”
Section: Introductionmentioning
confidence: 99%